NILAI TUKAR RUPIAH DAN SUKU BUNGA BANK INDONESIA TERHADAP INDEKS HARGA SAHAM GABUNGAN BURSA EFEK INDONESIA PERIODE 2012-2017 - Ardi Hidayat; Encep Saefullah (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2019)
The capital market can be used as a measure to see the back and forth of the dynamics of business in a country. The capital market aside from being a measure of the economy, the Composite Stock Price Index also reflects the economic conditions of a country. This study aims to find out how much influence the rupiah exchange rate and Bank Indonesia interest rates have on the Composite Stock Price Index. This research is a descriptive study with a quantitative approach method. The data used are secondary data, namely monthly data on the rupiah exchange rate, Bank Indonesia interest rates, and the Composite Stock Price Index as many as 67 data, namely the period 2012 to July 2017. The partial test results showed that the rupiah exchange rate had a significant positive effect on the Composite Stock Price Index. Joint Stock, this is indicated by the value of -test <-table = -3.3346 <-1.997 and a significance value of 0.001 <0.05. From the results of simultaneous testing the rupiah exchange rate and Bank Indonesia interest rates have a significant positive effect on the Composite Stock Price Index, this is indicated by the value of Fcount> Ftabel = 21.827> 3.14 and a significance value of 0.000 <0.05. The conclusion of this study partially, the rupiah exchange rate had a positive and significant effect on the Composite Stock Price Index, Bank Indonesia interest rates had a negative and significant effect on the Composite Stock Price Index. Simultaneously the rupiah exchange rate and Bank Indonesia interest rates have a positive and significant effect on the Composite Stock Price Index